REKAYASA PEMBUATAN MESIN PELET KAYU DAN PENGUJIAN HASILNYA - Djeni Hendra (Jurnal Penelitian Hasil Hutan, 2012)
Stock of fossil fuel will be decrescasing in the coming years accordingly, finding other raw material from renewable sources especially wood waste has to be sought. This material can be used as beat, electricity, transportation and directly used as fuel wood. However, phirycal properties of biomass, particularly sawdust has low density, difficult to store and transport. This problemscan be solved by converting sawdust into wood pelletusing a bat brydraulic press machine. The objective of this study was to make wood pellet machine and testing characteristics of the wood pellets. The machine has been succesfully made with production capacity of 2.67 kg/ b. Ramwmaterial sused in these research were sawdust of Tectona grandis, Paraserianthes falcataria and Acacia auriculiformis with particle size of 60 and 80 mesh. These materials were then machined into wood pellets at three stages of temperatures, ie. 150, 180 and 250°C respectively. Evaluation of wood pellet quality included moisture content, ash content, volatile matter, calorific value, density and pressure strength. The results showed that the bigbest quality of wood pellet was abtained from teak sawdust of size 80 meshand press temperature of 250 CThis process produced condition wood pellet with moisture content of 0.98%, asb content 0,93, volatile matter 80.63%%, density 0.82 g/cm', pressure strength 387,64 kg/cmi and calorific value of 4961.51 cal/g. Productivity of wood pellet machineis 2.67 kg with electric energy consumption of 2,55 kWh per hour.